What swimming coaches should know about atrial fibrillation and cardiac health - Henrich, T.; Soukup, G. (Journal of Swimming Research, 2012)
atrial fibrillation (AF) in competitive master swimmers (females and males) and possible relationships to training history, individual and family cardiac history, and associated medications and the use of methyl xanthenesas ergogenic aids. Masters swimmers have been reporting AF at increasing rates. This study wanted to determine if this group had a higher incidence of AF when compared to non -exercising age matched master swimmers as well as age matched individuals involved in other sport or exercise activity. Some sources of AF could be related to training history, family cardiac health history, and the use of methyl xanthenes and Beta -2 agonists as ergogenic aids. Since many swimmers have asthma, we wanted to determine whether combining Beta -2 agonist asthma medications with methylxanthines would be useful in predicting atrial fibrillation in master swimmers. Another question examined was whether the use of methyl xanthe nes could impact AF when used in combination with Beta-2 agonists. Creatine monohydrate (CM) has been shown to have a positive effect on recovery from coronary artery artificially induced occlusion and reduced fibrillation during and after the occlusion period. The researchers also propose to examine whether ingestion of vitamins like B6, B12, Coenzyme Q10 and Hawthorn extract resulted in lower incidences of AF or cardiac problems reported by master swimmer.